Методи діагностики вроджених патологій опорно-рухового апарату у дітей - Овченко, А. С. (ХНУРЭ, 2017)
In recent years, there has been a significant increase in the defect of the musculoskeletal system in newborns. Many of these children, despite improving methods of treatment, remain severely disabled and need constant external help. The most common anomalies in the development of the musculoskeletal system are: hip dysplasia or congenital dislocation, congenital clubfoot, congenital torticollis. Early and accurate diagnosis of the abnormalities of the musculoskeletal system will allow to achieve correct anatomical and functional development.
Keywords: опорно-руховий апарат